2021
DOI: 10.3390/ma14071753
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Copper Surface Oxidation and Reduction on Shear-Bond Strength Using Functional Monomers

Abstract: This study was conducted to clarify the influence of the copper surface oxidation and reduction on the shear-bond strength with functional monomers. Unheated copper specimens (UH; n = 88) were wet-ground. Three-quarters of the UH were then heated (HT). Two-thirds of the HT was then immersed in a hydrochloric acid solution (AC). Half of the AC was then reheated (RH). Each group was further divided into two groups (n = 11), which were primed by either 6-methacryloyloxyhexyl 2-thiouracil-5-carboxylate (MTU-6) or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 30 publications
(30 reference statements)
1
2
0
Order By: Relevance
“…As shown in Figure 2d, the high-resolution XPS Cu LMM peaks observed at 565.1, 576.3, and 578.6 can be assigned to Cu(I), Cu(II), and Cu(0), respectively. 38,39 These observations confirm that Cu(II) is the primary oxidation state in the sample TiO 2 /CuO obtained under air, whereas Cu species predominantly form Cu(I) and Cu(0) oxidation states in the sample TiO 2 /Cu x O/C under Ar/H 2 O.…”
Section: Aqysupporting
confidence: 65%
“…As shown in Figure 2d, the high-resolution XPS Cu LMM peaks observed at 565.1, 576.3, and 578.6 can be assigned to Cu(I), Cu(II), and Cu(0), respectively. 38,39 These observations confirm that Cu(II) is the primary oxidation state in the sample TiO 2 /CuO obtained under air, whereas Cu species predominantly form Cu(I) and Cu(0) oxidation states in the sample TiO 2 /Cu x O/C under Ar/H 2 O.…”
Section: Aqysupporting
confidence: 65%
“…The IV contained copper to improve its mechanical strength. The copper in the alloy was also oxidized; previous reports suggested that MDP could be effective against the oxidized copper contained in noble-metal alloys [18,19,24,25].…”
Section: Discussionmentioning
confidence: 99%
“…From the peak characteristics in the Ni 2p 3/2 core level spectra, the peaks at 852.9 ± 0.3, 854.6 ± 0.2, and 856.2 ± 0.4 eV, corresponding to metallic nickel, NiO (Ni 2+ ), and Ni­(OH) 2 (Ni 2+ ), , respectively, were found in all Ni–Cu/MS­( x ) catalysts. With the Cu 2p 3/2 core level spectra, the XPS spectra of all NiCu/MS­( x ) catalysts were deconvoluted into three Gaussian peaks at 932.4 ± 0.6 and 934.3 ± 1.1 eV, ascribed to the reduced copper species (Cu 0 /Cu + ) and CuO (Cu 2+ ), , respectively. NiO and CuO peaks were found in all reduced catalysts, probably due to unavoidable air oxidation of the catalyst during loading into the instrument.…”
Section: Resultsmentioning
confidence: 99%